Antibacterial bio-based composite film and preparation method thereof
Through the combination of nano-titanium dioxide modified tea polyphenols and polylactic acid, the problem of insufficient antibacterial and mechanical properties of bio-based films is solved, and efficient antibacterial effect and green and environmentally friendly film preparation is achieved, which significantly improves the antibacterial rate and mechanical properties. .
Patent Information
- Application Number
- CN202411464205.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The existing bio-based films have insufficient antibacterial properties, especially the poor dispersion of nanotitanium dioxide, resulting in poor antibacterial effects, and the tea polyphenols are volatile and utilizing low.
Nanotitanium dioxide modified tea polyphenols are combined with polylactic acid, and antibacterial biomass composite films are prepared through specific chemical modification and dispersion processes to reduce the agglomeration of nanotitanium dioxide and improve the compatibility and utilization of tea polyphenols.
It significantly improves the antibacterial properties and mechanical properties of biomass composite films, has excellent antibacterial effects and green environmental protection characteristics, the antibacterial rate can reach 99.9%, and the tensile strength can reach 40.3MPa.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thin films, in particular to an antibacterial bio-based composite film and a preparation method thereof. Background Art
[0002] Polylactic acid is a material with good biodegradability and biocompatibility. It is renewable, has high gloss and good transparency. It can be degraded into carbon dioxide and water under the action of microorganisms and acids. However, its antibacterial properties are not good, and the antibacterial properties of the bio-based film prepared from it are also not good. In recent years, the safety issues caused by microbial contamination have affected people's health. The development of bio-based films with antibacterial properties is the focus of current research.
[0003] Tea polyphenols are a safe and non-toxic green compound with excellent antibacterial and antioxidant properties. They are widely used in the food processing industry, the medical field, and the daily necessities field. Nano titanium dioxide, also known as nano titanium dioxide, has a small particle size and can reduce oxygen in water to produce highly oxidizing hydrogen peroxide and free radicals, which can decompose the cell outer membrane, followed by chaos in the cytoplasm and cell membrane until the cell dies, thereby achieving an antibacterial effect. However, due to its small particle size, it is easy to agglomerate. Therefore, how to improve the dispersion of nano titanium dioxide and thus improve the antibacterial effect is a hot topic of research. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a bio-based composite film which is both antibacterial and green and environmentally friendly and a preparation method thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is: an antibacterial bio-based composite film, the composite film comprises the following components in parts by weight: 100 parts of polylactic acid, 1-5 parts of nano-titanium dioxide modified tea polyphenols;
[0006] The preparation method of the antibacterial bio-based composite film is as follows:
[0007] Polylactic acid and nano-titanium dioxide modified tea polyphenols are added to chloroform, fully stirred and dispersed, poured onto a smooth glass plate, and cast and scraped using a scraping machine, and dried to obtain an antibacterial bio-based composite film.
[0008] Furthermore, the preparation method of the nano-titanium dioxide modified tea polyphenols is:
[0009] (1) Add formaldehyde and chloroform into a flask, stir and disperse, heat to 55-65° C., add 3-aminopropyltriethoxysilane, then heat to 75-85° C., add p-hydroxyphenylacetic acid, stir and react for 1-3 hours, cool to room temperature after the reaction, and evaporate the solvent to obtain an intermediate 1; the amount ratio of formaldehyde, 3-aminopropyltriethoxysilane, and p-hydroxyphenylacetic acid is (0.4-0.5) g:(1.5-2) g:1 g;
[0010] Formaldehyde, 3-aminopropyltriethoxysilane, and p-hydroxyphenylacetic acid undergo a Mannich reaction to obtain intermediate 1. The reaction process is shown below:
[0011]
[0012] (2) adding the intermediate product 1 and chloroform into a flask, stirring and dispersing, then adding thionyl chloride thereto, heating to 60-65° C., reacting for 2-5 hours, and after the reaction is completed, distilling under normal pressure and drying to obtain the intermediate product 2; the amount ratio of the intermediate product 1 to thionyl chloride is 1 g: (0.25-0.35) g;
[0013] The carboxyl group on the intermediate product 1 molecule undergoes chlorination reaction with thionyl chloride to obtain the intermediate product 2. The reaction process is as follows:
[0014]
[0015] (3) Add dried nano-titanium dioxide and ethanol to a flask, disperse by ultrasonication, add intermediate product 2 thereto, react by ultrasonication at 35-45° C. for 2-4 hours, centrifuge after the reaction is complete, wash with ethanol, centrifuge again, repeat 2-3 times, and dry to obtain intermediate product 3; the dosage ratio of nano-titanium dioxide to intermediate product 2 is 1 g:(1.5-4) g;
[0016] The silicon-oxygen bond of the intermediate product 2 is hydrolyzed to generate silicon hydroxyl groups, which are dehydrated and condensed with the hydroxyl groups on the nano-titanium dioxide to obtain the intermediate product 3. The reaction process is shown below;
[0017] in It is nano titanium dioxide;
[0018] (4) adding tea polyphenols and ethyl acetate into a flask, stirring to dissolve, then adding pyridine and intermediate product 3 thereto, reacting at 65-75° C. for 6-10 hours, washing with deionized water after the reaction, extracting and separating, rotary evaporating, and drying to obtain nano-titanium dioxide modified tea polyphenols; the amount ratio of tea polyphenols, pyridine, and intermediate product 3 is 1 g: (0.1-0.2) mL: (2.5-5) g;
[0019] Under the action of pyridine, -COCl2 on the intermediate product 3 molecule and the hydroxyl group on the tea polyphenol molecule undergo esterification reaction to obtain nano-titanium dioxide modified tea polyphenol. The reaction process is as follows:
[0020]
[0021] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0022] 1. The bio-based composite film prepared by the present invention contains inorganic nanoparticles such as titanium dioxide, which has good photocatalytic antibacterial effect, but is easy to agglomerate. The present invention reacts it with the intermediate product 2 to reduce the degree of agglomeration, increase its compatibility with organic matter, and can be evenly dispersed in the matrix. When subjected to external force, it can induce cracks in the matrix, and at the same time, the expansion of the matrix cracks is hindered and passivated, and finally the cracks are prevented from continuing to develop, thereby improving the mechanical properties of the film.
[0023] 2. The tea polyphenols used in the present invention are natural antibacterial substances, but tea polyphenols are volatile during the application process and have a low utilization rate. The present invention reacts the tea polyphenols with the intermediate product 3 to reduce volatility and improve the utilization rate of the tea polyphenols. The tea polyphenols and nano titanium dioxide assist each other to jointly improve the antibacterial and mechanical properties of the bio-based composite film. The composite film prepared by the present invention has the advantages of excellent antibacterial and mechanical properties and green environmental protection. DETAILED DESCRIPTION
[0024] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0025] Example 1
[0026] (1) 3 g of formaldehyde and 100 mL of chloroform were added to a flask, stirred and dispersed, heated to 60° C., 14 g of 3-aminopropyltriethoxysilane was added thereto, and the temperature was further raised to 80° C., 7.6 g of p-hydroxyphenylacetic acid was added thereto, and the mixture was stirred and reacted for 2 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was evaporated to obtain an intermediate product 1.
[0027] (2) 20 g of intermediate product 1 and 100 mL of chloroform were added to a flask, stirred and dispersed, and then 6 g of dichlorothionyl was added thereto. The mixture was heated to 60° C. and reacted for 4 h. After the reaction was completed, the mixture was distilled at atmospheric pressure and dried to obtain intermediate product 2.
[0028] (3) 2 g of dried nano-titanium dioxide and 200 mL of ethanol were added to a flask and ultrasonically dispersed. 8 g of intermediate product 2 was added thereto and ultrasonically reacted at 40° C. for 4 h. After the reaction was completed, the mixture was centrifuged, washed with ethanol, and centrifuged again. The reaction was repeated twice and dried to obtain intermediate product 3.
[0029] (4) 2 g of tea polyphenols and 100 mL of ethyl acetate were added to a flask and stirred to dissolve. Then, 0.2 mL of pyridine and 10 g of intermediate product 3 were added thereto. The mixture was reacted at 75° C. for 8 h. After the reaction was completed, the mixture was washed with deionized water, extracted, separated, rotary evaporated, and dried to obtain nano-titanium dioxide-modified tea polyphenols.
[0030] (5) Add 20 g of polylactic acid and 0.2 g of nano-titanium dioxide-modified tea polyphenols into 100 mL of chloroform, stir and disperse them thoroughly, pour them onto a smooth glass plate, use a film scraper to cast the film, and dry them to obtain an antibacterial bio-based composite film.
[0031] Example 2
[0032] (1) 3.8 g of formaldehyde and 100 mL of chloroform were added to a flask, stirred and dispersed, heated to 65° C., 11.4 g of 3-aminopropyltriethoxysilane was added thereto, and the temperature was further raised to 85° C., 7.6 g of p-hydroxyphenylacetic acid was added thereto, and the reaction was stirred for 1 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was evaporated to obtain an intermediate product 1.
[0033] (2) 20 g of intermediate product 1 and 100 mL of chloroform were added to a flask, stirred and dispersed, and then 7 g of dichlorothionyl was added thereto. The mixture was heated to 65° C. and reacted for 2 h. After the reaction was completed, the mixture was distilled at atmospheric pressure and dried to obtain intermediate product 2.
[0034] (3) 2 g of dried nano-titanium dioxide and 200 mL of ethanol were added to a flask and ultrasonically dispersed. 4 g of intermediate product 2 was added thereto and ultrasonically reacted at 45° C. for 2 h. After the reaction was completed, the mixture was centrifuged, washed with ethanol, and centrifuged again. The reaction was repeated 3 times and dried to obtain intermediate product 3.
[0035] (4) 2 g of tea polyphenols and 100 mL of ethyl acetate were added to a flask and stirred to dissolve. Then, 0.3 mL of pyridine and 6 g of intermediate product 3 were added thereto. The mixture was reacted at 65° C. for 10 h. After the reaction was completed, the mixture was washed with deionized water, extracted, separated, rotary evaporated, and dried to obtain nano-titanium dioxide-modified tea polyphenols.
[0036] (5) Add 20 g of polylactic acid and 0.4 g of nano-titanium dioxide-modified tea polyphenols into 100 mL of chloroform, stir and disperse them thoroughly, pour them onto a smooth glass plate, use a film scraper to cast the film, and dry them to obtain an antibacterial bio-based composite film.
[0037] Example 3
[0038] (1) 3.5 mL of formaldehyde and 100 mL of chloroform were added to a flask, stirred and dispersed, heated to 55° C., 15.2 g of 3-aminopropyltriethoxysilane was added thereto, and the temperature was raised to 75° C., 7.6 g of p-hydroxyphenylacetic acid was added thereto, and the reaction was stirred for 3 h. After the reaction was completed, the flask was cooled to room temperature, and the solvent was evaporated to obtain an intermediate product 1.
[0039] (2) 20 g of intermediate product 1 and 100 mL of chloroform were added to a flask, stirred and dispersed, and then 5 g of dichlorothionyl was added thereto. The mixture was heated to 65° C. and reacted for 5 h. After the reaction was completed, the mixture was distilled at atmospheric pressure and dried to obtain intermediate product 2.
[0040] (3) 2 g of dried nano-titanium dioxide and 200 mL of ethanol were added to a flask and ultrasonically dispersed. 7 g of intermediate product 2 was added thereto and ultrasonically reacted at 40° C. for 3 h. After the reaction was completed, the mixture was centrifuged, washed with ethanol, and centrifuged again. The reaction was repeated 3 times and dried to obtain intermediate product 3.
[0041] (4) 2 g of tea polyphenols and 100 mL of ethyl acetate were added to a flask and stirred to dissolve. Then, 0.4 mL of pyridine and 5 g of intermediate product 3 were added thereto. The mixture was reacted at 70° C. for 6 h. After the reaction was completed, the mixture was washed with deionized water, extracted, separated, rotary evaporated, and dried to obtain nano-titanium dioxide-modified tea polyphenols.
[0042] (5) Add 20 g of polylactic acid and 0.6 g of nano-titanium dioxide-modified tea polyphenols into 100 mL of chloroform, stir and disperse them thoroughly, pour them onto a smooth glass plate, use a film scraper to cast the film, and dry them to obtain an antibacterial bio-based composite film.
[0043] Example 4
[0044] (1) 3.8 g of formaldehyde and 100 mL of chloroform were added to a flask, stirred and dispersed, heated to 65° C., 12 g of 3-aminopropyltriethoxysilane was added thereto, and the temperature was further raised to 85° C., 7.6 g of p-hydroxyphenylacetic acid was added thereto, and the mixture was stirred and reacted for 3 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was evaporated to obtain an intermediate product 1.
[0045] (2) 20 g of intermediate product 1 and 100 mL of chloroform were added to a flask, stirred and dispersed, and then 5 g of dichlorothionyl was added thereto. The mixture was heated to 65° C. and reacted for 4 h. After the reaction was completed, the mixture was distilled at atmospheric pressure and dried to obtain intermediate product 2.
[0046] (3) Add 2 g of dried nano-titanium dioxide and 200 mL of ethanol into a flask and disperse by ultrasonication. Then add 3 g of intermediate product 2 and react by ultrasonication at 35°C for 3 h. After the reaction is completed, centrifuge, wash with ethanol, centrifuge again, repeat 3 times, and dry to obtain intermediate product 3.
[0047] (4) 2 g of tea polyphenols and 100 mL of ethyl acetate were added to a flask and stirred to dissolve. Then, 0.3 mL of pyridine and 8 g of intermediate product 3 were added thereto. The mixture was reacted at 75° C. for 8 h. After the reaction was completed, the mixture was washed with deionized water, extracted, separated, rotary evaporated, and dried to obtain nano-titanium dioxide-modified tea polyphenols.
[0048] (5) Add 20 g of polylactic acid and 0.8 g of nano-titanium dioxide-modified tea polyphenols into 100 mL of chloroform, stir and disperse them thoroughly, pour them onto a smooth glass plate, use a film scraping machine to cast the film, and dry them to obtain an antibacterial bio-based composite film.
[0049] Example 5
[0050] (1) 3.6 g of formaldehyde and 100 mL of chloroform were added to a flask, stirred and dispersed, heated to 60° C., 14 g of 3-aminopropyltriethoxysilane was added thereto, and the temperature was further raised to 80° C., 7.6 g of p-hydroxyphenylacetic acid was added thereto, and the mixture was stirred and reacted for 2 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was evaporated to obtain an intermediate product 1.
[0051] (2) 20 g of intermediate product 1 and 100 mL of chloroform were added to a flask, stirred and dispersed, and then 6 g of dichlorothionyl was added thereto. The mixture was heated to 65° C. and reacted for 4 h. After the reaction was completed, the mixture was distilled at atmospheric pressure and dried to obtain intermediate product 2.
[0052] (3) Add 2 g of dried nano-titanium dioxide and 200 mL of ethanol into a flask and disperse by ultrasonication. Then add 6 g of intermediate product 2 and react by ultrasonication at 45 °C for 2 h. After the reaction is completed, centrifuge, wash with ethanol, centrifuge again, repeat twice, and dry to obtain intermediate product 3.
[0053] (4) 2 g of tea polyphenols and 100 mL of ethyl acetate were added to a flask and stirred to dissolve. Then, 0.3 mL of pyridine and 7 g of intermediate product 3 were added thereto. The mixture was reacted at 75° C. for 10 h. After the reaction, the mixture was washed with deionized water, extracted, separated, rotary evaporated, and dried to obtain nano-titanium dioxide-modified tea polyphenols.
[0054] (5) Add 20 g of polylactic acid and 1 g of nano-titanium dioxide-modified tea polyphenols into 100 mL of chloroform, stir and disperse them thoroughly, pour them onto a smooth glass plate, use a film scraper to cast the film, and dry them to obtain an antibacterial bio-based composite film.
[0055] Comparative Example 1
[0056] 20 g of polylactic acid and 0.2 g of nano-titanium dioxide were added to 100 mL of chloroform, fully stirred and dispersed, poured onto a smooth glass plate, and cast and scraped using a scraper, and dried to obtain an antibacterial bio-based composite film.
[0057] Comparative Example 2
[0058] 20 g of polylactic acid and 0.2 g of tea polyphenols were added to 100 mL of chloroform, fully stirred and dispersed, poured onto a smooth glass plate, and cast and scraped using a scraper, and dried to obtain an antibacterial bio-based composite film.
[0059] Determination of antibacterial rate: According to QB / T2591-2003, the bio-based composite film was cut into a standard size of 50mm×50mm, and a 40mm×40mm polyethylene film was used as a covering film. A pipette was used to take 200μL of bacterial solution on the antibacterial film, and the sterilized polyethylene film was covered on it. The film was cultured at 37°C for 24h, and then the film was taken out and the bio-based composite film and polyethylene film were washed with eluent. After the mixture was shaken thoroughly, 100μL was inoculated in nutrient agar medium and cultured at 37°C for 24h. According to GB / T4789.2, the number of viable bacteria was tested and the antibacterial rate was calculated. The test bacteria were Escherichia coli and Staphylococcus aureus.
[0060] Table 1:
[0061]
[0062] It can be seen from the table that the bio-based composite film prepared by the present invention has excellent antibacterial effect, and the highest antibacterial rate against Escherichia coli and Staphylococcus aureus can reach 99.9%.
[0063] The tensile properties of the bio-based composite film were tested according to GB / T1040-2006. The film size was 15 mm × 15 mm and the tensile rate was 50 mm / min.
[0064]
[0065]
[0066] It can be seen from the table that the bio-based composite film prepared by the present invention has good mechanical properties, and the maximum tensile strength can reach 40.3 MPa.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An antibacterial bio-based composite film, characterized in that: The composite film comprises the following components in parts by weight: 100 parts of polylactic acid and 1-5 parts of nano-titanium dioxide modified tea polyphenols; The preparation method of the antibacterial bio-based composite film is as follows: Polylactic acid and nano-titanium dioxide modified tea polyphenols are added to chloroform, fully stirred and dispersed, poured onto a smooth glass plate, and cast and scraped using a scraping machine, and dried to obtain an antibacterial bio-based composite film.
2. The antibacterial bio-based composite film according to claim 1, characterized in that: The preparation method of the nano-titanium dioxide modified tea polyphenols is: (1) Add formaldehyde and chloroform into a flask, stir and disperse, heat to 55-65° C., add 3-aminopropyltriethoxysilane, then heat to 75-85° C., add p-hydroxyphenylacetic acid, stir and react for 1-3 hours, cool to room temperature after the reaction, and evaporate the solvent to obtain an intermediate product 1; (2) Add the intermediate product 1 and chloroform into a flask, stir and disperse, then add dichlorothionyl thereto, heat to 60-65° C., react for 2-5 hours, and after the reaction is completed, distill under normal pressure and dry to obtain the intermediate product 2; (3) Add dried nano-titanium dioxide and ethanol to a flask, disperse by ultrasonication, add intermediate product 2, react by ultrasonication at 35-45° C. for 2-4 h, centrifuge after the reaction is complete, wash with ethanol, centrifuge again, repeat 2-3 times, and dry to obtain intermediate product 3; (4) Add tea polyphenols and ethyl acetate into a flask, stir to dissolve, then add pyridine and intermediate 3, react at 65-75° C. for 6-10 hours. After the reaction is completed, wash with deionized water, extract and separate, rotary evaporate, and dry to obtain nano-titanium dioxide modified tea polyphenols.
3. The antibacterial bio-based composite film according to claim 2, characterized in that: In the above (1), the usage ratio of formaldehyde, 3-aminopropyltriethoxysilane and p-hydroxyphenylacetic acid is (0.4-0.5) g:(1.5-2) g:1 g.
4. The antibacterial bio-based composite film according to claim 2, characterized in that: In the method (2), the usage ratio of the intermediate product 1 and thionyl chloride is 1 g:(0.25-0.35) g.
5. The antibacterial bio-based composite film according to claim 2, characterized in that: In the above (3), the usage ratio of nano titanium dioxide and intermediate product 2 is 1g:(1.5-4)g.
6. The antibacterial bio-based composite film according to claim 2, characterized in that: In the above (4), the usage ratio of tea polyphenols, pyridine and intermediate product 3 is 1 g: (0.1-0.2) mL: (2.5-5) g.
Citation Information
Patent Citations
Composite medical chitosan / polycaprolactone film and preparation method thereof
CN104448739A
Environment-friendly thermal-insulation plastic film and preparation process thereof
CN109553945A
Calcium alginate coated tea polyphenol modified nanoparticles, sun-screening agent composition and preparation method of sun-screening agent composition
CN115887245A
Polyurethane adhesive with high cohesiveness and application of polyurethane adhesive in aluminum plastic film
CN118496799A
